2020
DOI: 10.9734/irjpac/2020/v21i430161
|View full text |Cite
|
Sign up to set email alerts
|

Extracting and Studying the Factors Affecting the Tanning Material in the Garad Pods

Abstract: In this study the chemical structure of Garad tan pods (acacia – nilotica) were determined and investigated. It was found that Garad tan is a polyphenol type of structure and consequently it has an antiseptic effect, it is also used as pretaning and retaning agent. Garad pods need to be disintegrated and ground into fine grains of very small diameter. In its powder form it cannot be used in tannage as the grains may block the sewage, hence, it has to be leached, concentrated and spray dried. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Since vegetable tannins are anions in nature [8], they react preferably with amino groups, either protonated or unprotonated rather than carboxyl groups of the collagen [9]. Although several studies have reported the tanning capacity and interaction mechanism of the extract from different plant species [9][10][11][12][13], they represent infinitesimal fraction of available potential of the vegetable tannin sources. Therefore, there is huge reservoir of unexploited plants from different parts of the world with significant amount of tannins that need to be studied for their chemistry as well as their potential industrial applications including in the leather industry.…”
Section: Introductionmentioning
confidence: 99%
“…Since vegetable tannins are anions in nature [8], they react preferably with amino groups, either protonated or unprotonated rather than carboxyl groups of the collagen [9]. Although several studies have reported the tanning capacity and interaction mechanism of the extract from different plant species [9][10][11][12][13], they represent infinitesimal fraction of available potential of the vegetable tannin sources. Therefore, there is huge reservoir of unexploited plants from different parts of the world with significant amount of tannins that need to be studied for their chemistry as well as their potential industrial applications including in the leather industry.…”
Section: Introductionmentioning
confidence: 99%